STRATEGI ENDORSEMENT SELEBRITI KOREA SELATAN DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN: PERAN BRAND IMAGE SEBAGAI MEDIATOR - Imani, Felia Fajar; Henryanto, Aria Ganna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
A South Korean celebrity endorser who's getting consumers to believe what's being advertised so they can give a good brand image to the product. This research will discuss one of the local body care products that uses a Celebrity endorser. The method in this research is positivist, quantitative with deductive data analysis. The questionnaire was distributed online with the help of a G-form media of 166 respondents obtained from the age range of 13-30 years, who are domiciled in Surabaya, and are users of Scarlett Whitening. The test results of the hypothesis suggest that celebrity endorsers can influence the brand image of a product. Furthermore, the Celebrity endorser has a significant influence on the purchase decision seen from the hypothesis test. A good brand image will make the consumer decide to buy. Finally, through hypothesis testing, the results showed that brand image has an influence in mediating celebrity endorsers against purchasing decisions. Recommendations for further research, that is, it is expected to develop other variables to study further in research about celebrity endorsers, brand image, and purchasing decisions as well as can expand the scope of research to be able to develop this research that is carried out only in one city.